2020
DOI: 10.1248/bpb.b19-01060
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Vasculitis Induced in Mice by the Cell Wall Mannoprotein of <i>Candida krusei</i>

Abstract: Kawasaki disease (KD) is an inflammatory disease that was identified by Professor Tomisaku Kawasaki in 1961. Candida albicans-derived substances, such as the hot water extract of C. albicans (CADS) and Candida water-soluble fraction (CAWS), induced coronary vasculitis similar to KD in mice. An increasing proportion of deep-seated candidiasis cases are caused by non-albicans Candida and are often resistant to antifungal drugs. We herein investigated whether the hot water extract of C. krusei, inherently resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 64 publications
2
6
0
Order By: Relevance
“…We demonstrated that the vasculitis activity of CAWS negatively corelated with the presence of β-mannose residues 11,12) . We also confirmed that coronary vasculitis was induced by the hot water extract (HWE) of the standard strains of Candida albicans, Candida metapsilosis, and Candida krusei [13][14][15][16] . Chemical and NMR spectral analyses strongly suggested that the major polysaccharide component of HWE is the cell wall mannan, thus the vasculitis activity might be strongly related to the presence and the structure of mannan moiety [13][14][15][16] .…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…We demonstrated that the vasculitis activity of CAWS negatively corelated with the presence of β-mannose residues 11,12) . We also confirmed that coronary vasculitis was induced by the hot water extract (HWE) of the standard strains of Candida albicans, Candida metapsilosis, and Candida krusei [13][14][15][16] . Chemical and NMR spectral analyses strongly suggested that the major polysaccharide component of HWE is the cell wall mannan, thus the vasculitis activity might be strongly related to the presence and the structure of mannan moiety [13][14][15][16] .…”
Section: Introductionsupporting
confidence: 66%
“…We also confirmed that coronary vasculitis was induced by the hot water extract (HWE) of the standard strains of Candida albicans, Candida metapsilosis, and Candida krusei [13][14][15][16] . Chemical and NMR spectral analyses strongly suggested that the major polysaccharide component of HWE is the cell wall mannan, thus the vasculitis activity might be strongly related to the presence and the structure of mannan moiety [13][14][15][16] . CAWS-vasculitis, particularly in DBA/2 mice, is severe and ultimately results in death due to cardiac hypertrophy 12,17,18) .…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations